CHARACTERIZATION AND PHARMACEUTICAL EVALUATION OF DAUCUS CAROTA PECTIN AS A SUSPENDING AGENT IN ORAL DOSAGE FORMS - Frederick William Akuffo Owusu; Prince George jnr Acquah; Mariam El Boakye-Gyasi; Marcel Tunkumgnen Bayor; Desmond Asamoah Bruce Otu; Sarah Amankra Meta; Ama Amankwah Adu-Boampong (International Journal of Pharmacy & Integrated Health Sciences)
Background: Suspensions are equilibrated two-phased thermodynamically unstable systems increasingly used in the stability and bioavailability enhancement of a myriad of drug substances. Biodegradable, biocompatible and cost-effective biopolymers such as pectin are becoming popular alternative suspending agents to decrease sedimentation and ensure uniformity and accuracy in drug dosing. Nevertheless, limited commercial pectin sources with ideal gelling properties necessitate the search for novel sources such as carrots, a versatile vegetable.  Objectives: The study therefore centred on the characterization and pharmaceutical evaluation of the suspending qualities of Daucus carota (carrot) pectin acquired from the conventional acid extraction procedure. Methodology: Fresh carrots were acquired, authenticated and processed before pectin extraction. The pectin extracted was characterized and evaluated for phytochemical properties such as proximate composition and degree of esterification. Different concentrations (1% and 2%) of carrot pectin and acacia gum (as a standard) were utilized in formulating paracetamol suspensions as suspending agents. Results: The pectin yield was 11.6% and contained glycosides, tannins, saponins, and phenols. FTIR analysis identified all the essential pectin functional groups while other characterization parameters showed quality high methoxyl pectin. Carrot pectin suspensions demonstrated significantly (P < 0.01) lower re-dispersibility and sedimentation rate when compared to acacia. The flow rate and sedimentation volumes were however non-significantly different. Conclusion: The characterization and suspending properties of carrot pectin have been successfully evaluated. Ultimately, acacia gum can be substituted with carrot pectin as a suspending agent.